Comparative Analysis of Applications of Selected Mobile Payment Systems in Poland - Chmielarz, Witold (Advanced Information Technologies for Management – AITM 2009, 2009)
The basic aim of this article is to evaluate mobile payments used in Poland with regard to their usefulness as compared with card payments and bank transfers. First, research principles and procedure have been formulated. Next, the author conducted analyses and presented detailed characteristics of the obtained findings. In the last part of this paper the author presented a summary, conclusions as well as further directions for development of m-payments in Poland, which have been formulated in the study.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 28-39